Nanotransethosomes for enhanced transdermal delivery of mangiferin against rheumatoid arthritis: formulation, characterization, invivo pharmacokinetic and pharmacodynamic evaluation. (31st December 2023) - Adin, Syeda Nashvia; Gupta, Isha; Rashid, Md Abdur; Alhamhoom, Yahya; Aqil, Mohd; Mujeeb, Mohd
Abstract: The present research study limns the preparation of MNF loaded transethosomes (MNF-TE) to improve MNF solubility, bioavailability and permeation through skin layers for transdermal delivery. MNF-TE was formulated using thin-film hydration method and optimization was done using Box-Behnken design (BBD). MNF-TEopt was characterized for Polydispersity index (PDI), vesicle size, entrapment efficiency, zeta potential and in vitro MNF release. For further evaluation, Pharmacokinetic study, Transmission electron microscopy (TEM), Skin permeation study and Confocal scanning laser microscopy (CLSM) were performed withal. The MNF-TEopt presented spherical and sealed shape vesicles with small vesicle size of 148.6 nm, entrapment efficiency of 74.23%, PDI of 0.1139 and in vitro release of 65.32%. The CLSM study unveiled that the developed formulation has greater permeation of MNF across the skin layers in comparison with the MNF suspension gel. The pharmacokinetic study demonstrated Cmax and AUC0-24 h of 6.94 ± 0.51 μg/ml and 43.92 ± 7.90 μg.h/ml via transdermal route in comparison to Cmax and AUC0-24 h of 3.74 ± 1.91 μg/ml and 22.96 ± 9.76 μg.h/ml presented by MNF-TE oral administration. The in vivo study revealed that the MNF-TE gel has good anti-arthritic potential in comparison with the standard diclofenac gel which was evinced by radiographic analysis and histopathological studies. Further, skin irritation study on Wistar albino rats confirm that the developed MNF-TE formulation is safer for skin application. The current investigation corroborated that the prepared TE vesicle formulation is a treasured carrier for the MNF transdermal delivery for the management of rheumatoid arthritis.